The value of traditional African religious music into liturgy: Lobethal Congregation - Lebaka, Morakeng E. K. (HTS teologiese studies, 2015)
The purpose of this study was to discover whether the integration of traditional African religious music into Evangelical Lutheran liturgical church services, could effect a change in member attendance and/or participation. To achieve this, the study employed direct observation, video recordings and informal interviews. In addition, church records of attendance during Holy Communion once a month between 2008 and 2013 were accessed. The study was done at the Evangelical Lutheran Church of the Lobethal Congregation (Arkona Parish, Northern Diocese, Sekhukhune District, Limpopo Province, South Africa). It was demonstrated that church attendance increased dramatically after traditional African religious music was introduced into the Evangelical Lutheran liturgical services in 2011. Observations and video recordings showed that drums, rattles, horns and whistles were used. Handclapping was seen to act almost as a metronome, which steadily maintained the tempo. It was concluded that introducing traditional African religious music into Evangelical Lutheran liturgical church services has increased attendance and participation of church members. Therefore, the introduction of African religious music could be considered for other Evangelical Lutheran congregations in Africa.